Timing of CGM initiation in pediatric diabetes: The CGM TIME Trial. Issue 2 (4th November 2020) - Lawson, Margaret L.; Verbeeten, Kate C.; Courtney, Jennilea M.; Bradley, Brenda J.; McAssey, Karen; Clarson, Cheril; Kirsch, Susan; Curtis, Jacqueline R; Mahmud, Farid H; Richardson, Christine; Cooper, Tammy; Chan, Jason; et al.
Abstract: Objective: To determine whether timing of CGM initiation offering low glucose suspend (LGS) affects CGM adherence in children and youth starting insulin pump therapy. Methods: A 5‐site RCT of pump‐naïve subjects (aged 5‐18 years) with type 1 diabetes (T1D) for at least 1 year compared simultaneous pump and CGM initiation offering LGS vs standard pump therapy with CGM initiation delayed for 6 months. Primary outcome was CGM adherence (hours per 28 days) (MiniMed™ Paradigm™ Veo™ system; CareLink Pro™ software) over 6 months after CGM initiation. Secondary outcome HbA1c was measured centrally. Linear mixed‐models and ordinary least squares models were fitted to estimate effect of intervention, and covariates baseline age, T1D duration, HbA1c, gender, ethnicity, hypoglycemia history, clinical site, and association between CGM adherence and HbA1c. Results: The trial randomized 144/152 (95%) eligible subjects. Baseline mean age was 11.5 ± 3.3(SD) years, T1D duration 3.4 ± 3.1 years, and HbA1c 7.9 ± 0.9%. Six months after CGM initiation, adjusted mean difference in CGM adherence was 62.4 hours per 28 days greater in the Simultaneous Group compared to Delayed Group ( P = .007). There was no difference in mean HbA1c at 6 months. However, for each 100 hours of CGM use per 28‐day period, HbA1c was 0.39% (95% CI 0.10%‐0.69%) lower. Higher CGM adherence was associated with reduced time with glucose >10 mmol/L ( P  < .001). Conclusion: CGM adherence was higher after 6 months when initiated at same time as pump therapy compared to starting CGM 6 months after pump therapy. Greater CGM adherence was associated with improved HbA1c.